Alpinia zerumbet (Pers.): Food and medicinal plant with potential in vitro and in vivo anti-cancer activities - Hussein Zahra, Maram; Salem, Tarek A.R.; El-Araag, Bishoy; Yosri, Nermeen; EL-Ghiban, Samah; Zaki, Kholoud; H. Marei, Amel; Abd El_Wahed, Aida; Saeed, Aamer; Khatib, Alfi; Alajmi, Mohamed Fahad; M. Shatili, Abdulrahman; et al. (MDPI AG, 2019)
Background/Aim: Plants play an important role in anti-cancer drug discovery, therefore, the current study aimed to evaluate the biological activity of Alpinia zerumbet (A. zerumbet) flowers. Methods: The phytochemical and biological criteria of A. zerumbet were in vitro investigated as well as in mouse xenograft model. Results: A. zerumbet extracts, specially CH2Cl2 and MeOH extracts, exhibited the highest potent anti-tumor activity against Ehrlich ascites carcinoma (EAC) cells. The most active CH2Cl2 extract was subjected to bioassay-guided fractionation leading to isolatation of the naturally occurring 5,6-dehydrokawain (DK) which was characterized by IR, MS, 1H-NMR and 13C-NMR. A. zerumbet extracts, specially MeOH and CH2Cl2 extracts, exhibited significant inhibitory activity towards tumor volume (TV). Furthermore, A. zerumbet extracts declined the high level of malonaldehyde (MDA) as well as elevated the levels of superoxide dismutase (SOD) and catalase (CAT) in liver tissue homogenate. Moreover, DK showed anti-proliferative action on different human cancer cell lines. The recorded IC50 values against breast carcinoma (MCF-7), liver carcinoma (Hep-G2) and larynx carcinoma cells (HEP-2) were 3.08, 6.8, and 8.7 µg/mL, respectively. Conclusion: Taken together, these findings open the door for further investigations in order to explore the potential medicinal properties of A. zerumbet.